Persepsi Remaja Laki-Laki Dan Perempuan Tentang Seks Pra Nikah Di SMA Negeri 6 Denpasar - Ayu Vira Sadvika Vidanti; Ni Komang Yuni Rahyani; Ni Luh Putu Sri Erawati (Poltekkes Kemenkes Denpasar, 2018)
Adolescent are one period towards adulthood. At this time, there are various problems faced, including curiosity and trial and error. The aim of the study is to describe perception of male and female adolescence about premarital sexual among high school students in Denpasar City. This study is a descriptive study that applies probability sampling technique and systematic random samplig method. This study was conducted on April 28 2019. The population of this study are 321, 11th grade students at Senior High School 6 Denpasar which consists of 139 male students and 112 female students. The data were collected by using questionnaire and analyzed by using distribution frequency. We found that, out of 139 male students, 70 (50,4%) have negative perceptions about premarital sexual and out of 112 female students, 66 (60,7%) have negative perceptions about premarital sexual. The school is expected to give counseling in regards to the effects of premarital sexual in order to reduce the occurrence of premarital sexual at Senior High School 6 Denpasar.